R40.76 binds to the α domain of ZO-1: role of ZO-1 (α+) in epithelial differentiation and mechano-sensing. Issue 3 (3rd July 2019) - Rouaud, Florian; Vasileva, Ekaterina; Spadaro, Domenica; Tsukita, Sachiko; Citi, Sandra
ABSTRACT: The barrier function of epithelia and endothelia depends on tight junctions, which are formed by the polymerization of claudins on a scaffold of ZO proteins. Two differentially spliced isoforms of ZO-1 have been described, depending on the presence of the α domain, but the function of this domain is unclear. ZO-1 also contains a C-terminal ZU5 domain, which is involved in a mechano-sensitive intramolecular interaction with the central (ZPSG) region of ZO-1. Here we use immunoblotting and immunofluorescence to map the binding sites for commercially available monoclonal and polyclonal antibodies against ZO-1, and for a new polyclonal antibody (R3) that we developed against the ZO-1 C-terminus. We demonstrate that antibody R40.76 binds to the α domain, and the R3 antibody binds to the ZU5 domain. The (α+) isoform of ZO-1 shows higher expression in epithelial versus endothelial cells, and in differentiated versus undifferentiated primary keratinocytes, suggesting a link to epithelial differentiation and a potential molecular adaptation to junctions subjected to stronger mechanical forces. These results provide new tools and hypotheses to investigate the role of the α and ZU5 domains in ZO-1 mechano-sensing and dynamic interactions with the cytoskeleton and junctional ligands.